Analysis of the physics book for the sixth grade, scientific/applied, according to issues of science, technology, education sciences, and educational sciences. - قدوري, سعد (Journal of College of Education, 2023)
This research aims to analyze the physics textbook for the sixth scientific / applied grade according to the issues of science, technology, society and the environment according to the issues of science, technology, society and the environment included in the content of the physics book for the sixth scientific / applied grade , and the range of knowldeg students of it .       To achieve the goal of the research, a list of issues of science, technology, society and the environment was prepared and presented to a group of experts, and the list consisted in its final form of (10) main issues and (50) sub-issues, and the content of the physics textbook for the sixth scientific / applied grade was analyzed based on the list that was prepared.Be bult the test to knowledge the students with issius since , technology society and  environment it contain (20) form multy choice          The data were collected and statistically analyzed by appropriate statistical means, and the research reached the following results: The physics textbook for the sixth scientific / applied grade has a decent content of science, technology, society, and environment issues.The students in sixth stage since/applecation have good level in issius sicience , technlology , society and the environment .In light of these results, a set of conclusions, recommendations and proposals were developed.